2011
DOI: 10.1037/2160-4096.1.s.63
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress in children and adolescents exposed to family violence: I. Overview and issues.

Abstract: Exposure to child physical abuse and parents' domestic violence can subject youth to pervasive traumatic stress and can lead to posttraumatic stress disorder (PTSD). This article presents evolving conceptualizations in the burgeoning field of trauma related to family violence exposure and describes how the often repeating and ongoing nature of family violence exposure can complicate a PTSD diagnosis. In addition, recent literature indicates that children exposed to family violence may experience problems in mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 45 publications
1
67
1
5
Order By: Relevance
“…Bolton et al found that, once again, PTSD-related symptoms of avoidance, numbing, and hypervigilence can deleteriously affect academic performance [2], and research with adolescents has found associations between PTSD and school truancy and suspensions [39]. Adolescents with PTSD show slower processing of incoming information and difficulties in concentration and decision-making, which can have negative consequences for functioning in school [39].…”
Section: Work and Academic Performancementioning
confidence: 99%
“…Bolton et al found that, once again, PTSD-related symptoms of avoidance, numbing, and hypervigilence can deleteriously affect academic performance [2], and research with adolescents has found associations between PTSD and school truancy and suspensions [39]. Adolescents with PTSD show slower processing of incoming information and difficulties in concentration and decision-making, which can have negative consequences for functioning in school [39].…”
Section: Work and Academic Performancementioning
confidence: 99%
“…Por otro lado, coincidiendo con Bair-Merritt et al (2006), Grych et al (2000), Jaffe et al (2002), Kernick et al (2003), Kitzmann et al (2003), Margolin & Vickerman (2007), y Sternberg et al (2006), los problemas que presentan son tanto internalizantes (ansiedad/depresión, retraimiento, quejas somáticas) como externalizantes (agresividad). Los resultados del estudio indican también que ambos sexos se ven afectados negativamente, coincidiendo con Maxwell y Maxwell (2003), aunque en este estudio son las niñas las que presentan mayor afectación coincidiendo con los resultados de Lemmy et al (2001) y Sternberg et al (1993); si bien las diferencias sólo son estadísticamente significativas en el síndrome empírico Problemas Sociales.…”
Section: Discusión Y Conclusionesunclassified
“…Sternberg et al (2006) apuntan que los menores expuestos a violencia de género tienen una probabilidad dos veces mayor que los menores no expuestos de presentar problemas internalizantes o emocionales (ansiedad, depresión y somatizaciones), y externalizantes o problemas de conducta (conducta no normativa y agresión). En esta línea, numerosos estudios documentan tasas elevadas en ambos tipos de problemas (Bair-Merritt, Blackstone, & Feudtner, 2006;Grych, Jouriles, Swank, McDonald, & Norwood, 2000;Jaffe, Moffitt, Caspi, Taylor, & Arseneault, 2002;Kernick, Wolf, Holt, McKnight, Huebner, & Rivara, 2003;Kitzmann, Gaylord, Holt, & Kenny, 2003;Margolin & Vickerman, 2007), incluso cuando otros factores de riesgo son controlados (Hazen, Connelly, Kelleher, Barth, & Landsverk, 2006). Grych et al (2000), con una muestra de 228 hijos/as de mujeres maltratadas en casas de acogida (8 y 14 años), encontraron que el 21% revelaron problemas externalizantes y señalaron que estos eran más comunes que los internalizantes.…”
Section: Introductionunclassified
“…6 Therefore, subjective responses should be evaluated to understand how and to what extent traumatic events affect a child's life. 7 The Child Posttraumatic Cognitions Inventory (cPTCI), 8 an adaptation of the Posttraumatic Cognitions Inventory (PTCI) 9,10 for children and adolescents, assesses negative posttraumatic appraisals of events in this population. The cPTCI is intended to provide information about a potentially significant mechanism in the development of PTSD in children and adolescents, as well as to be a clinically useful tool for the assessment and prediction of this disorder.…”
Section: Introductionmentioning
confidence: 99%